Effect of maternal position on fetal behavioural state and heart rate variability in healthy late gestation pregnancy. (11th December 2016) - Stone, Peter R.; Burgess, Wendy; McIntyre, Jordan P. R.; Gunn, Alistair J.; Lear, Christopher A.; Bennet, Laura; Mitchell, Edwin A.; Thompson, John M. D.; ,
Abstract : Key points: Fetal behavioural state in healthy late gestation pregnancy is affected by maternal position. Fetal state 1F is more likely to occur in maternal supine or right lateral positions. Fetal state 4F is less likely to occur when the woman lies supine or semi‐recumbent. Fetal state change is more likely when the woman is supine or semi‐recumbent. Fetal heart rate variability is affected by maternal position with variability reduced in supine and semi‐recumbent positions. Abstract: Fetal behavioural states (FBS) are measures of fetal wellbeing. In acute hypoxaemia, the human fetus adapts to a lower oxygen consuming state with changes in the cardiotocograph and reduced fetal activity. Recent studies of late gestation stillbirth described the importance of sleep position in the risk of intrauterine death. We designed this study to assess the effects of different maternal positions on FBS in healthy late gestation pregnancies under controlled conditions. Twenty‐nine healthy women had continuous fetal ECG recordings under standardized conditions in four randomly allocated positions, left lateral, right lateral, supine and semi‐recumbent. Two blinded observers, assigned fetal states in 5 min blocks. Measures of fetal heart rate variability were calculated from ECG beat to beat data. Compared to state 2F, state 4F was less likely to occur when women were semi‐recumbent [odds ratio (OR) = 0.11, 95% confidence interval (95% CI) 0.02, 0.55], and supine (OR = 0.27, 95% CI 0.07, 1.10). State 1F was more likely on the right (OR = 2.36, 95% CI 1.11, 5.04) or supine (OR = 4.99, 95% CI 2.41, 10.43) compared to the left. State change was more likely when the mother was semi‐recumbent (OR = 2.17, 95% CI 1.19, 3.95) or supine (OR = 2.67, 95% CI 1.46, 4.85). There was a significant association of maternal position to mean fetal heart rate. The measures of heart rate variability (SDNN and RMSSD) were reduced in both semi‐recumbent and supine positions. In healthy late gestation pregnancy, maternal position affects FBS and heart rate variability. These effects are likely fetal adaptations to positions which may produce a mild hypoxic stress. Key points: Fetal behavioural state in healthy late gestation pregnancy is affected by maternal position. Fetal state 1F is more likely to occur in maternal supine or right lateral positions. Fetal state 4F is less likely to occur when the woman lies supine or semi‐recumbent. Fetal state change is more likely when the woman is supine or semi‐recumbent. Fetal heart rate variability is affected by maternal position with variability reduced in supine and semi‐recumbent positions.